Efficacy and safety of acupuncture on oligomenorrhea due to polycystic ovary syndrome: An international multicenter, pilot randomized controlled trial. Issue 7 (18th February 2022) - Park, Kyoung Sun; Gang, Weijuan; Kim, Pyung-Wha; Yang, Changsop; Jun, Purumea; Jung, So-Young; Kwon, Ojin; Lee, Jin Moo; Lee, Hye Jeong; Lee, Su Jeong; Jing, Xianghong; Zhang, Ning; et al.
Abstract: Background: Polycystic ovary syndrome (PCOS) is one of the most common disorders of reproductive endocrinology affecting women of reproductive age. Our study aims to explore the feasibility of a full-scale trial to evaluate the efficacy and safety of acupuncture for PCOS. Methods: This study is a two-armed, parallel, multi-country, multi-center, pilot randomized controlled trial (RCT) for PCOS with oligomenorrhea. We will recruit 60 women aged 20 to 40 years with oligomenorrhea due to PCOS. The participants will be randomly assigned to acupuncture and control groups. The acupuncture group will undergo a total of 40 sessions for 16 weeks with usual care. The control group will be managed with usual care (regular meals, sufficient sleep, and appropriate exercise) only. The primary clinical outcome is mean change in menstrual frequency from baseline to 16 weeks and 32 weeks (follow-up) after the start of the trial. The secondary outcomes are menstrual period, levels of estradiol, luteinizing hormone (LH), follicle-stimulating hormone (FSH), and total testosterone, LH/FSH ratio, antral follicle count and ovarian volume, body mass index, waist hip ratio, acne severity, and health-related quality of life questionnaire scores at 16 and 32 weeks after the start of the trial. Discussion: This is the first protocol for multi-country, multi-center RCTs for PCOS in Korea and China. The control group in this study will be subjected to usual care (regular meals, enough sleep, and appropriate exercise). The results of this study will provide evidence for future clinical decisions and guidelines. This trial has been registered at ClinicalTrials.gov (Identifier: NCT04509817).